A Perplexing case of isolated abducens nerve palsy in a primigravida woman: A case report - Johnna M. Caputo; Marianna Catege; Ishani Dev; Benjamin Souferi; Adele El Kareh (Case Reports in Women's Health, 2023)
Isolated abducens nerve palsy is a rare presentation in women during pregnancy. When an abducens nerve palsy is elicited in a pregnant woman, work-up should start with labs and neuroimaging to rule out mechanical and organic causes such as tumors, preeclampsia, and multiple sclerosis. This case report highlights a 35-year-old woman, gravida 1, para 0, who was sent to the local medical center by her ophthalmologist at 37 weeks of gestation due to a left-sided headache and blurry vision. Upon admission, work-up was negative for preeclampsia. Tick-borne disease panel and lumbar puncture were unrevealing. No other mechanical or lab abnormalities were elicited. Magnetic resonance venography revealed a diminutive left transverse sinus, left sigmoid sinus, and left internal jugular vein in comparison with the right, indicating a possible congenital variant. Labor was induced to see if this would alleviate the patient's abducens nerve palsy. After induction of labor and initiation of dexamethasone, the patient's sixth cranial nerve palsy began to improve.